Web-Based Geometry Application Information System as a Learning Media - S, Cornelius; Manek, Patricia Gertrudis (Department of Information Technology, Universitas Timor, Indonesia, 2024)
This research aims to design and develop a Web-Based Geometry Application Information System as an interactive learning medium. The application is crafted to enhance students' understanding of geometric concepts through the use of interactive and visual web technology. The system development method involves stages such as needs analysis, interface design, application development, and user evaluation. The application provides various learning concepts, including basic geometry, area calculations, and visual simulations to aid students in grasping geometric abstractions. Evaluation is conducted through field trials involving students and teachers, focusing on learning effectiveness, user interface, and user satisfaction. The research outcomes are expected to contribute to the development of innovative mathematics learning technology, facilitating the geometry learning process.